2013
DOI: 10.1002/jor.22567
|View full text |Cite
|
Sign up to set email alerts
|

Foot and ankle joint movements inside orthoses for children with spastic CP

Abstract: We compared the ankle joint and foot segment kinematics of pediatric cerebral palsy (CP) participants walking with and without orthoses. A six segment foot model (6SF) was used to track foot motion. Holes were cut in the study orthoses so that electromagnetic markers could be directly placed on the skin. The Hinged Ankle Foot Orthoses (HAFO) allowed a significant increase in ankle dorsiflexion as compared to the barefoot condition during gait, but significantly constrained sagittal forefoot motion and forefoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Contrary to previous reports, the SMO showed no effects in the coronal plane. However, our study demonstrated immediate effects of an orthosis intervention [10].…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…Contrary to previous reports, the SMO showed no effects in the coronal plane. However, our study demonstrated immediate effects of an orthosis intervention [10].…”
Section: Introductionmentioning
confidence: 53%
“…Although most SAFOs allow some ankle dorsiflexion, some have proposed that HAFOs provide a more natural kinematic and kinetic function [6,9]. Our previous study investigated the immediate effects of orthoses and confirmed that SAFO constrained forefoot range of motion (ROM) and did not control excessive plantar flexion [10]. Contrary to previous reports, the SMO showed no effects in the coronal plane.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…[1][2][3][4] It has been reported that it can capture both of the elemental and oxidized forms of mercury vapors by possible mercuric sulfide (HgS) formation. 5 Among various sulfur functional groups generated from elemental sulfur on the activated carbon surface at a wide impregnation temperature window, the elemental sulfur functional group turned out to be the main sulfur form responsible for Hg(0) adsorption onto sulfur-impregnated activated carbon.…”
Section: Introductionmentioning
confidence: 99%